Interplay between peptide supply, peptide off-rate and levels of tapasin in cell surface presentation of peptides by MHC class I. (October 2022) - Boulanger, Denise; Douglas, Leon; James, Edd; Dalchau, Neil; Elliott, Tim
Abstract : Objective: Determining which peptides are presented by MHC-I, and in what proportion, has profound implications for developing effective treatments. However, our ability to predict peptide presentation levels is currently limited, especially in situations where biological factors influence peptide generation or expression levels of MHC-I and PLC components, as observed in tumours or inflammation. We have developed and validated a mechanistic model for predicting cell-surface presentation of competing peptides. The method explicitly modelled key steps in the processing of intracellular peptides, incorporating both peptide binding affinity and intracellular peptide abundance. We are now extending this model to include the regulation of tapasin expression and ERAP1 function to predict qualitative and quantitative changes in the immunopeptidome presented on tumour cells expressing low levels of these cofactors. Method: pMHC surface presentation of model peptides was measured by a flow cytometry assay in which wild type or TpnKO fibroblasts were transfected with one or 2 plasmids expressing a model pep- tide cleaved in the cytoplasm from a fluorescent fusion protein. To increase pMHC surface expression in TpnKO cells, these cells were treated (or not) with IFNγ and an ERAP inhibitor and transfected with a Tpn-Cerulean construct allowing relative quantitation of tapasin expression reported by Cerulean fluorescence intensity. Results: We showed that some peptides were not detectable on the surface of TpnKO cells even in the presence of IFNγ unless the cells were treated with an ERAP inhibitor. We can correlate the level of surface expression of peptides of different off-rate with their expression level in the cytoplasm and the level of tapasin expression. Conclusions: We have developed a triple transfection flow cytometry assay to quantitate competition between peptides in cells expressing different amount of tapasin. These data will be used to refine our predictive model and incorporate tapasin quantification and ERAP1 activity in the predictions.